Digitalisation and the economy - Luca Dedola; Michael Ehrmann; Peter Hoffmann; Ana Lamo; Gonzalo Paz Pardo; Jirka Slacalek; Georg Strasser (European Central Bank (ECB), 2023)
Digitalisation has fundamentally changed the global economy and will continue to do so. This paper draws on economic research to identify some of its key implications for labour markets, inequality, e-commerce and the financial system. Beyond its potential to boost productivity and living standards, digitalisation: i) does not necessarily replace jobs on aggregate but changes their content; ii) tends to raise income and wealth inequality; iii) has ambiguous effects on competition; and iv) might change how the retail and financial sectors respond to monetary policy. Developing adequate (re-)training opportunities and providing a labour market, regulatory, and innovation environment which encourages the creation of "good jobs" is essential to improve productivity and equity while avoiding a polarisation of labour markets. E-commerce and fintech will likely lead to a faster transmission of monetary policy. The rise of fintech brings about new risks for regulatory arbitrage and has ramifications for financial stability.
Keywords: D31; D4; E52; G2; 330; digitalisation; inequality; competition; e-commerce; fintech